1998
DOI: 10.1128/jvi.72.9.7115-7124.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Polyserine Tract of Herpes Simplex Virus ICP4 Is Required for Normal Viral Gene Expression and Growth in Murine Trigeminal Ganglia

Abstract: ICP4 of herpes simplex virus (HSV) is essential for productive infection due to its central role in the regulation of HSV transcription. This study identified a region of ICP4 that is not required for viral growth in culture or at the periphery of experimentally inoculated mice but is critical for productive growth in the trigeminal ganglia. This region of ICP4 encompasses amino acids 184 to 198 and contains 13 nearly contiguous serine residues that are highly conserved among the alphaherpesviruses. A mutant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Interestingly, polyserine domains were proposed to be involved in the targeting of proteins to the nucleus ( Wolf et al. 2013 ), and are also required for a normal viral gene expression ( Bates and DeLuca 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, polyserine domains were proposed to be involved in the targeting of proteins to the nucleus ( Wolf et al. 2013 ), and are also required for a normal viral gene expression ( Bates and DeLuca 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, we have not tested the ability of these mutants to support the growth of an ICP27-null mutant virus in cells of neuronal origin. Recently, it has been shown that deletion of a highly conserved polyserine tract found between residues 184 and 198 in HSV-1 ICP4 results in a virus that is marginally impaired for growth in culture and in the eyes of infected mice but is completely impaired for growth in the trigeminal ganglia (2,53). To address questions on specific functions and interactions of ICP27 during viral infection, the kinase consensus site mutations are being introduced into the viral genome by marker transfer.…”
Section: Discussionmentioning
confidence: 99%
“…The high copy number of viral genomes during latency has long been a concern for models in which no viral gene expression is envisaged, especially as the nonlinear form of the genome could represent replicated concatemeric DNA that is not packaged into virions, as well as circularized input DNA. In some systems, infection with mutants that do not replicate in neurons (such as TK − mutants) results in the retention of fewer genomes during latency (Efstathiou et al ., 1989 ; Sawtell, 1997 ; Bates & DeLuca, 1998 ; Kramer et al ., 1998 ). This may well be due entirely to differential loading of neurons from the periphery, but it is difficult to dismiss the suspicion that some latent genomes are retained after viral DNA replication has occurred in the neuron .…”
Section: A Late Block?mentioning
confidence: 99%